2007
DOI: 10.1097/01.sla.0000242712.74502.72
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/II Trial of 125I Methylene Blue for One-Stage Sentinel Lymph Node Biopsy

Abstract: This method eliminates the painful preoperative injections of Tc colloid, is performed by the surgeon in the operating room, is associated with lower radiation exposures for personnel, and avoids the delays caused by nonoperating room personnel. These observations warrant a more extensive trial of this method using the 1000-microCi dose of I methylene blue dye for sentinel lymph node biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In melanoma, gamma tracing of radioiodinated methylene blue confirmed the existence of approximately 80% of the lesions and enabled detection of secondary lesions in six of 12 patients. Alternatively, the radiolabel on methylene blue may be REVIEW: Luminescence-based Approaches in Interventional Molecular Imaging van Leeuwen et al used to provide radioguidance during lymphatic mapping, as was shown in an initial feasibility study in 12 women scheduled for breast cancer-based sentinel node biopsy (88). While the use of radiolabeled fluorescein and methylene blue indicates that iodination may be acceptable for small molecules, the success of ICG99m Tc-nanocolloid may also be representative for fluorescence labeling of large protein-based radiotracers such as antibodies.…”
Section: Hybrid Tracersmentioning
confidence: 96%
“…In melanoma, gamma tracing of radioiodinated methylene blue confirmed the existence of approximately 80% of the lesions and enabled detection of secondary lesions in six of 12 patients. Alternatively, the radiolabel on methylene blue may be REVIEW: Luminescence-based Approaches in Interventional Molecular Imaging van Leeuwen et al used to provide radioguidance during lymphatic mapping, as was shown in an initial feasibility study in 12 women scheduled for breast cancer-based sentinel node biopsy (88). While the use of radiolabeled fluorescein and methylene blue indicates that iodination may be acceptable for small molecules, the success of ICG99m Tc-nanocolloid may also be representative for fluorescence labeling of large protein-based radiotracers such as antibodies.…”
Section: Hybrid Tracersmentioning
confidence: 96%
“…Initial report of this study demonstrated 11 of 12 subjects with successful mapping, with a mean of 1.66 nodes per case and no adverse events. Further prospective studies have been proposed to demonstrate its equivalence to current techniques [18]. These dyes may be viable alternatives to the current standards.…”
Section: Methylene Bluementioning
confidence: 96%
“…While Varghese et al [11] noted temporary tattooing as the sole adverse effect of subdermal and subareolar injection of MB, some studies have reported no other adverse effects (Table II) [5,6,8]. In stark contrast, Stradling et al [7] were the first to note 5 of 24 patients who developed severe skin erythema, ulcers, and necrosis after intradermal injection of (21) 5 min breast massage Simmons et al [6] 5 cc intraparenchymal/peritumoral None reported 0/113 (0) 5 min breast massage Nour [8] 5 cc subareolar None reported 0/54 (0) 5 min breast massage Golshan and Nakhlis [9] 5 cc periareolar None reported 0/141 (0) 5 min breast massage Cundiff et al [10] 5 MB, prompting discontinuation of its injection close to skin, and noting no subsequent further inflammatory or necrotic complications with deeper injection. One deep injection of MB has been attributed to cause a capsular contracture around a breast implant with prosthetic staining, although this occurred 9 months after mastectomy [16], and to our knowledge has never again been reported.…”
Section: Discussionmentioning
confidence: 95%
“…One deep injection of MB has been attributed to cause a capsular contracture around a breast implant with prosthetic staining, although this occurred 9 months after mastectomy [16], and to our knowledge has never again been reported. Since that time, some authors of series without cutaneous manifestations attribute their lack of morbidity to the use of a deep intraparenchymal dye injection [9,10], and while there has been no systematic study directly comparing the two injection methods, it has been suggested that deeper injections may avoid this complication [9,10]. Zakaria et al [12] reviewed their complications from 401 patients having LM from MB dye, in which they noted "local inflammation" in 7 out of 43 patients having intraparenchymal injections, although these cases were not further characterized and comparison with the subareolar method in that same series is difficult to interpret because of the wide variations in volumes and dilutions throughout the series.…”
Section: Discussionmentioning
confidence: 99%